2005
DOI: 10.1111/j.1461-0248.2005.00785.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal stability of aquatic food webs: partitioning the effects of species diversity, species composition and enrichment

Abstract: Theory predicts that species diversity can enhance stability of community-level biomass while simultaneously decreasing population-level stability. Enrichment can theoretically destabilize communities but effects may become weaker with increasing diversity because of the inclusion of consumer-resistant prey. Few experiments using direct manipulations of species diversity have tested these predictions. We used laboratorybased aquatic food webs to examine the effects of species composition, diversity and enrichm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
130
4
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(153 citation statements)
references
References 37 publications
17
130
4
2
Order By: Relevance
“…C. closterium carried the recovery and, as in the 18°C control, dominated the community at the end of the experiment. The community response to the 22°C heat wave is consistent with experimental stability studies that found resilience to be related to the dominance of fast growing species (Steiner et al, 2005(Steiner et al, , 2006. Due to the differences in the performance of two diatom species, H′ during the 22°C heat wave and the recovery phase was slightly lower than in the control.…”
Section: Resistance and Resilience To Heat Wavessupporting
confidence: 72%
“…C. closterium carried the recovery and, as in the 18°C control, dominated the community at the end of the experiment. The community response to the 22°C heat wave is consistent with experimental stability studies that found resilience to be related to the dominance of fast growing species (Steiner et al, 2005(Steiner et al, , 2006. Due to the differences in the performance of two diatom species, H′ during the 22°C heat wave and the recovery phase was slightly lower than in the control.…”
Section: Resistance and Resilience To Heat Wavessupporting
confidence: 72%
“…The positive relationship between plant richness and community stability observed in this study was in agreement with the findings of many other studies [26,29,[35][36][37][38][39][40][41][42]. We further explored the possible mechanisms, and found that statistical averaging, overyielding, and component population effects were likely mechanisms to account for the stabilizing effect of plant richness.…”
Section: Discussionsupporting
confidence: 80%
“…It is worth noting that we found a positive relationship between population-and community-level stability. Previous studies reported positive [37,39,41], negative [26,29,40], and neutral relationships [36,38,42] between the two, but the causes of these different patterns are still unknown. Future work should examine the general nature of the relationships and elucidate the associated mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…This linkage is well documented in terrestrial systems (3)(4)(5)(6)(7) and is increasingly being established for marine systems (8)(9)(10)(11). Marine phytoplankton generate roughly half of global primary production (12)(13)(14) and play a critical role in oceanic ecosystem structure and function.…”
mentioning
confidence: 99%